Growth in Senegal : The 1995-2005 Experience - Ndiaye, Mansour (World Bank, Washington, DC, 2017)
Following several years of disappointing economic performance, Senegal has made an important turnaround, with real Gross Domestic Product (GDP) growth averaging over 5 percent annually during 1995-2005. This paper shows that macroeconomic and structural reforms are key factors explaining this recovery. Drivers of sound economic policy decisions in Senegal have included enhanced democratic processes, political commitment to the West African Economic and Monetary Union (WAEMU), and donor community conditionalities.